2015
DOI: 10.1039/c5ra22242g
|View full text |Cite
|
Sign up to set email alerts
|

The effects of viscoelastic properties on the cellular morphology of silicone rubber foams generated by supercritical carbon dioxide

Abstract: Silica content, saturation temperature and pressure all have an effect on silicone rubbers' viscoelastic properties, which further has a close connection with the cellular structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…The LCB-PLA foams produced by batch foaming process using CO 2 as foaming agents was described by Goel and Beckman earlier. 24 The samples with thickness of 0.4 mm were prepared by compression molding under vacuum at 180 C and then cut into the dimensions of 10 Â 10 mm 2 for foaming. The sample was then placed into a high-pressure vessel which was preheated to the experimental temperature.…”
Section: Preparation Of Lcb-pla Foams By Supercritical Comentioning
confidence: 99%
“…The LCB-PLA foams produced by batch foaming process using CO 2 as foaming agents was described by Goel and Beckman earlier. 24 The samples with thickness of 0.4 mm were prepared by compression molding under vacuum at 180 C and then cut into the dimensions of 10 Â 10 mm 2 for foaming. The sample was then placed into a high-pressure vessel which was preheated to the experimental temperature.…”
Section: Preparation Of Lcb-pla Foams By Supercritical Comentioning
confidence: 99%
“…When the precuring time of silicone rubber matrix is 10 min, the cell density reaches to the maximum value 2.96 × 10 10 cells/cm 3 . It is well known that with the extension of precuring time, the strength of silicone rubber matrix will be improved, leading to increasing of the viscosity . When the precuring time is short, the cure degree is so low that the strength of silicone rubber matrix cannot hold cell stability, which causes the cell to merge or collapse.…”
Section: Resultsmentioning
confidence: 99%
“…They first reported that the high temperature vulcanized (HTV) silicone rubber foams were prepared with scCO 2 . Liao et al investigated that the viscoelastic properties of silicone rubber play a vital role in the scCO 2 foaming process. Yang et al prepared the microcellular HTV silicone rubber foams by controlling the foaming parameters, and the smallest cell size could reached to 9.8 μm.…”
Section: Introductionmentioning
confidence: 99%
“…The primary challenge posed in foaming of rubbers stems from their elastic and soft (less rigid) structure. A limited number of studies that have appeared in the literature on foaming of silicone rubber with carbon dioxide show some of the challenges . These challenges include balancing the viscoelasticity, bubble growth and coalescence, and the need for pre‐and postfoaming curing.…”
Section: Introductionmentioning
confidence: 99%